2015
DOI: 10.1073/pnas.1501489112
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary feeding restructures urban bird communities

Abstract: Food availability is a primary driver of avian population regulation. However, few studies have considered the effects of what is essentially a massive supplementary feeding experiment: the practice of wild bird feeding. Bird feeding has been posited as an important factor influencing the structure of bird communities, especially in urban areas, although experimental evidence to support this is almost entirely lacking. We carried out an 18-mo experimental feeding study at 23 residential properties to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
173
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(185 citation statements)
references
References 48 publications
6
173
0
Order By: Relevance
“…Galbraith et al (2015) found greater abundances of introduced house sparrows and spotted doves at feeders in Auckland and reduced abundances of native species such as gray gerygones. While feeders clearly attract greater numbers of the species using them, they may also reduce species richness in the avian community because of the predominance of introduced species.…”
Section: Does Feeding Inevitably Change Urban Bird Community Structure?mentioning
confidence: 88%
See 3 more Smart Citations
“…Galbraith et al (2015) found greater abundances of introduced house sparrows and spotted doves at feeders in Auckland and reduced abundances of native species such as gray gerygones. While feeders clearly attract greater numbers of the species using them, they may also reduce species richness in the avian community because of the predominance of introduced species.…”
Section: Does Feeding Inevitably Change Urban Bird Community Structure?mentioning
confidence: 88%
“…Therefore, Australian feeder birds are far larger than those typically found at Northern Hemisphere feeders. In New Zealand, the situation is strongly influenced by the abundance of introduced species with the most common being house sparrows Passer domesticus (20-35 g), common blackbirds and common mynas Acridotheres tristis (82-140 g) with the only native species feeding on grain-based supplements being the silvereye Zosterops lateralis (9-17 g; Galbraith et al, 2015). In South Africa, while the diversity of birds visiting gardens is remarkably large-from diminutive waxbills (Estrildidae) to huge hornbills (Bucerotidae)-we could find no reliable data with which to compile a comparative list of the most common species observed at bird feeders.…”
Section: North Vs Southmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, people support birds with food in winter not only for conservation purposes, but also for aesthetic reasons, and most providers of food would like to know what is the most preferred food (Lott 1988;Cox and Gaston 2015) to attract more birds (Cowie and Hinsley 1988;Galbraith et al 2014Galbraith et al , 2015Cox and Gaston 2015). Feeding birds is probably among the most popular animal-human interactions (Jones and Reynolds 2008), and producing and selling bird food is still an increasing market (Buczacki 2007;Jones and Reynolds 2008).…”
Section: Introductionmentioning
confidence: 99%